Rancang Bangun Pembangkit Listrik Tenaga Picohydro Untuk Sistem Penerangan Jalan Umum 50Watt Berbasis Bluetooth HC-05 - Lukman Aditya; Rizky Prasetyo adi (JURNAL ELEKTRO, 2024)
The electricity needs is increased in line with economic growth, population growth and development growth. The energy of the water flowing in the tank can be utilized as a source of electrical energy by converting the micro-hydro electricity production system into public street lighting. It is on this basis that the authors raise the title design and build of a 50 Watt public street lighting control system with a Bluetooth Hc05-based Picohydro Power Plant (PHP). Data collection for the writing of this final report used observation and experiment (pilot study) methods. Measurement of data in the form of writing this final report is carried out to find out the results of the data so that it can be used for measurement. Calculation formula is used for measuring water discharge, measuring PHP power, and measuring water velocity. The fastest water flow velocity produced was 15.68 lpm at a height of 250 cm, for a height of 85 cm we obtained 11.18 lpm. The highest power produced by the micro hydro generator is 0.37 Watt with a height of 250 cm, at 85 cm of height can get 0.14 Watt. The power generated by the inverter is 64.26 Watt with a load of 50 Watt public street lighting, for testing the inverter without load, a power of 23 Watt is obtained and the farthest distance to be able to connect from the Bluetooth HC05 is 20 meters.